The rowing-specific reinvestment scale - Sparks, K. V.; Kavussanu, M.; Masters, R. S. W.; Ring, C. (Journal of Sports Sciences, 2022)
This research project aimed to develop and validate a rowing-specific reinvestment scale. In Study 1, a 24-item questionnaire was developed and the content validity was assessed using experts (N = 7) and pilot-tested in rowers (N = 24). Next, rowers (N = 282) completed the questionnaire with the remaining items, and exploratory factor analysis (EFA) was conducted. This further reduced the number of items and revealed two factors, rowing specific conscious motor processing (RS-CMP) and movement self-consciousness (RS-MSC). In Study 2, rowers (N = 270) completed the scale that was evaluated using confirmatory factor analysis (CFA). Moreover, the construct validity of the scale was investigated by asking them to complete measures of movement-specific reinvestment, perceived performance, self-consciousness, and state anxiety. Actual performance was also determined based on their race finishing position. Study 1 EFA resulted in a 2-factor model with six items assessing RS-CMP and six items assessing RS-MSC. Study 2 supported the factor structure of scale; CFA indicated an acceptable model fit with good internal consistency. Content validity was also supported, with evidence of concurrent, convergent, discriminant, and predictive validity. In conclusion, these studies provided good initial evidence for the validity and reliability of the RSRS.